PENGARUH POST-TREATMENT PLASMA CVD LAPISAN DIAMOND-LIKE CARBON TERHADAP SIFAT KEKERASAN PERMUKAAN BAJA AISI 410 - Wahyu Anhar; Nurwahidah Jamal; Suprapto Suprapto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
This study is aimed to determine the effect of post-treatment plasma CVD on diamond-like carbon films of surface hardness AISI 410 steel. Enhancement of surface hardness on AISI 410 can be done with deposition thin layer by plasma CVD, and continued by post-treatment plasma CVD. Mixture of Ar (90%) with CH4 (10%), and He (76%) with CH4 (24%) are used as thin layer material. Deposition parameter of pressure, temperature, and time that been used are 1.6 mbar, 300 °C, and 4 hours, respectively. Furthermore, post-treatment process parameter is used by Ar gas, with pressure of 1 mbar, temperature 300 °C, and variation time of 10, 20, 30 minutes. Surface hardness test is used by Vickers microhardness tester. Cross-section microstructure and chemical compositions are examined by scanning electron microscopy coupled with energy dispersive spectroscopy. Based on surface hardness test, the surface hardness on AISI 410 is increased by post-treatment process. The surface hardness from 232.3 VHN increase to 301.2 VHN is produced by post-treatment of compound Ar-CH4 in 20 minutes. Futhermore, the surface hardness from 1,035.8 VHN increase to 1,743.2 VHN is produced by post-treatment of compound He-CH4 in 30 minutes. Keywords: Post-treatment, Surface hardness, AISI 410, Ar-CH4, He-CH4